An associative analysis of recognition memory in humans - Ryan, Leona Bailey (2020)
Experiments in this thesis tested recognition memory tasks in human participants. Recognition memory tasks measure novelty preference when participants are exposed to familiar and novel stimuli. The majority of this research has been conducted using non-human animal samples, although there have been some experiments testing humans. The experiments in this thesis expand on and modify recognition memory tasks for humans. The experiments presented tested an associative model of recognition memory, as recognition memory can also be explained by other accounts. Recognition memory tasks were adapted for human participants by presenting images on a computer screen fitted with a non-invasive eye-tracker. Eye movements were recorded so dwell times could be used to determine if participants were spending more time looking at expected (familiar) or unexpected (novel) stimuli. It was predicted that humans would perform recognition memory tasks in a similar way to animals and that results would be best explained by the associative account (Wagner’s SOP model). The experiments in Chapter 2 did find support of a contextual learning task in human adults and children, which can be explained by the associative, declarative and generalisation decrement accounts. Experiments in Chapter 3 that sought to test the associative account by testing a Pavlovian manipulation known to affect learning, namely extinction, were unsuccessful. Experiments in Chapter 4 tested the associative model using spacing experiments that manipulate the time between sample presentations during training. These experiments were also unsuccessful. The conclusion of this thesis is that results from non-human animal studies suggest that the associative account better explains behaviour in recognition memory tasks, however the experiments presented in this thesis, which tested human participants, were unable to find evidence to support the associative account being superior at explaining behaviour in the tasks tested.